2016
DOI: 10.17334/jps.87709
|View full text |Cite
|
Sign up to set email alerts
|

Role of post-operative radiation therapy in single brain metastasis from clear cell sarcoma in children: a case report with systemic review

Abstract: IntroductionBrain metastasis is a common oncologic problem in adults but is relatively uncommon in children with solid tumors. In fact, approximately 25-35% of all adult cancer patients with solid tumors will develop parenchymal intracranial metastasis whereas only 2.5% to 4.5% of children will do [1][2][3][4][5]. Brain metastasis of clear cell sarcoma of the kidney occurs in less than 5% of cases during the follow-up [6,7]. Because of the relative rarity of this particular entity, information regarding manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The presence or absence of peritumoral vasogenic edema was not mentioned in those reports. 3,5 The absence of peritumoral edema in a metastatic brain lesion from CCSK has been reported so far by Shajpaul et al 4 A single large-sized frontal hemispheric metastatic lesion, in that case, showed no tumor-associated edema and no contrast-enhancement. Those features have been attributed to the poor vascularity and cellularity of that metastatic lesion by the authors, reflecting the histopathology of the primary tumor.…”
Section: Discussionmentioning
confidence: 55%
“…The presence or absence of peritumoral vasogenic edema was not mentioned in those reports. 3,5 The absence of peritumoral edema in a metastatic brain lesion from CCSK has been reported so far by Shajpaul et al 4 A single large-sized frontal hemispheric metastatic lesion, in that case, showed no tumor-associated edema and no contrast-enhancement. Those features have been attributed to the poor vascularity and cellularity of that metastatic lesion by the authors, reflecting the histopathology of the primary tumor.…”
Section: Discussionmentioning
confidence: 55%